ANGELA MILLION, CHRISTIAN HAID, IGNACIO CASTILLO ULLOA, NINA BAUR - Spatial Transformations. Kaleidoscopic Perspectives on the Refiguration of Spaces - Borrego Gómez-Pallete, Ignacio (ZARCH, 2024)
ANGELA MILLION, CHRISTIAN HAID, IGNACIO CASTILLO ULLOA, NINA BAURSpatial Transformations. Kaleidoscopic Perspectives on the Refiguration of SpacesTechnische Universität Berlin, London, 2021, 321 pp. Tapa blanda. 38,97 €Idioma: inglésISBN: 978-1-032-11453-8